Desa Jrgan, Surga Kesenian: Mengenal Budaya Lokal yang Unik - Laily Khayati; Vika Putri Zamanina; Muhamad Akhlis; Sri Lestari; Nur Isnaeni; Muhammad Faiz Ramadhan; Tri Buana Pamungkas; Ricky Prassetya; Firly Muliya Rahmadana; Sahar Wardani; Sofiyatul Mukaromah; Muhammad Ni'am Ali; Nurul Istianah; Salma Khusna Wahda; M. Trihudiyatmanto (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Art is a part of culture that is admired for its uniqueness and beauty. Art is a work of human art that expresses beauty and expresses the soul and culture of its creator. Community empowerment is an activity to increase community participation in providing the necessities of life and solving problems experienced by the community. The activities are carried out through the Community Service Lecture (KPM) program, which is a community service-based activity to increase student empathy for the conditions of society and the environment. This community service activity is carried out for 40 days starting from January to February 2025, and can be summarized as follows: Art is a work created by humans to enjoy its beauty and meaning which is the result of the creator's imagination and emotions. Every region in Indonesia has various kinds of art and culture that must be preserved. Especially in Jragan Village, which has so many varieties of art and culture that must be preserved. Providing outreach to children can foster their love for their own art and culture and they can preserve art and culture so that it does not become extinct. The arts in Jragan village include Kuda Lumping, Soreng, Gedruk, Barongsai and Bujang Ganong